Exploring the Relationship between Organizational Learning Capability, Trust, and Politics: An Empirical Study - Tirelli, Andrew (Université d'Ottawa / University of Ottawa, 2011)
A lack of research surrounding the contextual factors that either facilitate or impede the progress of developing learning capabilities in organizations suggests that researchers have yet to examine such issues. Indeed, despite a plethora of information on the trust, politics, and learning constructs, researchers have yet to explore these variables in conjunction with one another. While literature regarding organizational learning has grown substantially over the last decade, studies continue to investigate a common set of established factors that support the development of this practise. This study will explore the complex relationships between trust, politics, and learning, as well as the influence on building employee commitment and reducing turnover intentions. Results from the study provide the basis for the development of an integrative framework that illustrates how contextual factors influence organizational learning capability and in turn, the effects that developing learning capability can have on other organizational processes.
Keywords: Organizational Learning; Organizational Trust; Organizational Politics; Employee Commitment; Turnover; The Learning Organization